“It always gets pushed aside:” Qualitative perspectives on puberty and menstruation education in U.S.A. schools - Schmitt, Margaret L.; Gruer, Caitlin; Hagstrom, Christine; Ekua Adenu-Mensah, Nana; Nowara, Azure; Keeley, Katie; Sommer, Marni (Frontiers in Reproductive Health, 2022)
Adolescent girls in the U.S.A. often lack sufficient education on pubertal and menstrual health topics. This educational gap may be growing given the current decline in American elementary and middle schools’ delivery of sexual health education. Furthermore, little is known about the actual scope and quality of existing menstruation and puberty education in U.S.A. schools. This paper provides insights into some of the challenges with the delivery of menstruation and puberty education in schools. Qualitative and participatory research methodologies were utilized with Black and Latina girls ages 15-19 and adults working with youth in three U.S.A. cities (Chicago, Los Angeles, and New York City), exploring experiences of menstruation within school and family contexts. Findings revealed tension between school responsibility and family authority in providing menstruation and puberty education in schools, school- and teacher-related delivery challenges, and inadequate and disengaging menstruation and puberty content. Further research is needed on the effectiveness and best practices for providing this education in schools, including improved understanding on student and parent preferences, delivery mediums and the scope of content.